Dampak Perubahan Iklim pada Kualitas Tanah dan Air Dalam Geokimia Lingkungan - Haslindah Hasan (Jurnal Ilmiah Multidisiplin Amsir, 2025)
This research aims to reveal the impact of climate change on soil and water quality in Indonesia through an environmental geochemistry approach. By analyzing soil and water samples from several representative locations, the study found that rising temperatures and fluctuating rainfall contribute to a decrease in soil pH and an increase in heavy metal concentrations in water. Interviews with farmers and local communities showed a growing awareness of the changes occurring in agricultural patterns and resource quality. The findings of this study emphasize the importance of sustainable management and collaboration among researchers, government, and communities to address the challenges posed by climate change.